Penyuluhan Potensi Budidaya Tanaman Vanili (Vanilla Planifolia) Dalam Polybag Di Area Perkotaan Padat Penduduk Sebagai Penghasilan Tambahan Masyarakat Di Kelurahan Sooko, Kecamatan Sooko, Kabupaten Mojokerto - Soesanto Soesanto; Mega Darmi Novita; Joko Sri Mulyono; Yuni Rosita Dewi; Rissa Putri Masri (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
In 1819, the vanilla plant became known in Indonesia thanks to the Dutch. Finally, around the 1960s, Java became an area with rapid development in vanilla production. This has resulted in the emergence of many vanilla production centers, making Indonesia the fourth largest vanilla producing country in the world. Rapid urbanization in Mojokerto has created economic challenges for its residents, especially in dense areas such as Sooko Village, Sooko District, Mojokerto Regency. Cultivation of high-value crops such as vanilla is emerging as a potential solution to increase household income in the region. The author conducted community service in the form of outreach activities on the potential for cultivating vanilla plants (Vanilla planifolia) in polybags in densely populated urban areas as additional income for urban communities in Sooko Village, Sooko District, Mojokerto Regency. The aim is for people to understand how to easily cultivate vanilla in polybags and provide additional income for residents. This activity went smoothly and well according to plan. The community hopes that there will be similar activities or other variations in the future.